Context aware energy allocation by auction based method in wireless sensor networks - Shaheed, Imam Ush; Nodi, Sadia Sabrin (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.